HUBUNGAN BUDAYA ORGANISASI DAN KOMUNIKASI ORGANISASI DENGAN KINERJA GURU - Najmulmunir, Nandang; Hasyim, Abd. Wahid; Triana, Ema (Program Studi Magister Pendidikan Islam Universitas Islam 45, 2009)
The objective of the research is to study the organizational culture and organizational communication on teacher?s performance. This research is done at school SDIT Kecamatan Bekasi Utara. The Research was conducted with N = 56 teachers. This research used survey method, and the method based on multistage random sampling. The population teachers in this district are 125 teachers, and 10% from them in about 56 teachers. Three instruments for getting data above are point analysis, test validity by correlation product moment and of reliability with alpha cronbach. The data analysis research which correlation technique and double regression technique. The research concludes that there is a positive relationship between: (1) culture organization (X1) and teachers performance (Y) with ?y1 = 0,394 and ?= 48.683 + 0,329X1; (2) organizational communication (X2) and teachers performance with ?y2 = 0,377 and ?= 39.825 + 0,446X2. Furthermore there is a positive relationship between those two independent variab les with teachers performance with ?y.12 = 0,473 and ?= 28.818 + 0,253X1 + 0,329X2.